2021
DOI: 10.3390/ijerph182312510
|View full text |Cite
|
Sign up to set email alerts
|

The Living Space: Psychological Well-Being and Mental Health in Response to Interiors Presented in Virtual Reality

Abstract: There has been a recent interest in how architecture affects mental health and psychological well-being, motivated by the fact that we spend the majority of our waking time inside and interacting with built environments. Some studies have investigated the psychological responses to indoor design parameters; for instance, contours, and proposed that curved interiors, when compared to angular ones, were aesthetically preferred and induced higher positive emotions. The present study aimed to systematically examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 72 publications
3
9
0
Order By: Relevance
“…Earlier research, however, has identified sex differences, linking contour preference and sketch production to symbolic representations of the human body morphology ( Munroe et al, 1976 ). Similar tendencies were also observed in a previous study from our lab, where a significant positive effect of angular rooms (on cognitive performance and subjective ratings of affect and spatial experience) was found in male when compared to female participants ( Tawil et al, 2021 ). However, to date, no study has yet attempted to examine these differences in contours evaluation with interior design stimuli.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Earlier research, however, has identified sex differences, linking contour preference and sketch production to symbolic representations of the human body morphology ( Munroe et al, 1976 ). Similar tendencies were also observed in a previous study from our lab, where a significant positive effect of angular rooms (on cognitive performance and subjective ratings of affect and spatial experience) was found in male when compared to female participants ( Tawil et al, 2021 ). However, to date, no study has yet attempted to examine these differences in contours evaluation with interior design stimuli.…”
Section: Introductionsupporting
confidence: 91%
“…When comparing with traditional presentation modes, evidence on the curvature effect in virtual environments seems inconsistent. Empty virtual rooms with curved boundaries were found to elicit more pleasantness and arousal than those with linear boundaries ( Banaei et al, 2017 ), while no effects were observed in another study where participants were immersed in photo-realistic virtual interiors ( Tawil et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Based on the aforementioned literature, we predicted that the walk in nature would have a more beneficial effect for amygdala activity in women compared to men. Furthermore, based on the previous studies showing that exposure to nature is beneficial for attention and cognitive capacity ( Berman et al, 2008 ; Ohly et al, 2016 ; Stevenson et al, 2018 ), and taking into account the importance of exploring interindividual differences such as sex when investigating the effects of man-made environments on cognition ( Tawil et al, 2021 ), we predicted that cognitive performance on the MIST would improve after the nature compared to the urban walk and examined potential sex differences.…”
Section: Introductionmentioning
confidence: 99%